Design and simulate a rectangular patch microstrip antenna for bluetooth system / Aida Andila Jabli - Jabli, Aida Andila (2017)
The main purpose of this project is to design, simulate, fabricate and measure a single rectangular patch antenna at microwave frequency range. This project used computer aided design (CAD) package for designing and simulation before the fabrication process of the designed antenna is being made. The antenna was designed and simulated using CST Studio Suite 2006. CST Microwave Studio is a folly featured software package for electromagnetic analysis and design in the high frequency range. After the fabrication process, the antenna is measured using Vector Network Analyzer (VNA). The results obtained will be compared with the simulation results. The antenna is designed to operate at Bluetooth system operating frequency of 2.4-2.484GHz.